PENGEMBANGAN BAHAN AJAR PAI DENGAN MODEL PENDIDIKAN BERPARADIGMA PROFETIK - Anam, Choirul (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Abstract: The article discusses the development of teaching materials of PAI with propheticparadigm of educational model approach. As known, the essence of Islamic teachingsincluded: belief, Shari'ah and morals. Three cores of Islamic teachings are then translatedin the form of Rukun Iman, Pillars of Islam and Morals. And of the three was born SciencesTauhid, Fiqh Arts and Sciences Morals. The third group of religious knowledge is thenfitted with a discussion of the fundamentals of Islam hkum, namely; al-Quran and al-Hadith,and coupled with the history of Islam (dates), so that the start sequence Tauhid Science /Faith, Science Fiqh / Shari'ah, the Quran and al-Hadith, Morals, and Date /Islam history.To that end, teaching materials PAI largely abstract philosophical difficult to establish ascientific approach, akliyah. However, in accordance with their specialization, teachingmaterials of PAI was mostly abstract philosophical difficult to establish a scientificapproach, akliyah. Therefore, the ability and skills of educators to mengkongkritkanabstract material was very necessary, although it was not easy. Criteria for selection anddevelopment of teaching materials of PAI, at the lack of six criteria that the material Festiveof PAI should be able to fill the state philosophy of Pancasila, prioritizes teachingfundamental and thorough, in accordance with the level of development and maturity of thechild, adapted to the environment that they are meaningful to the lives of children daily -day. taught on the level and type of school / madrasah should be terminal. given to everyeducational institution should be a continuous, integrated and aligned. Prophet Muhammadis a true learner and professor of world civilization, he gave the example of holistic learningmethod, so the selection of teaching materials of PAI should and should refer to him as amodel.Keywords: Subjects, Approach, Prophetic